From attitudes and practices to policy: Reflections on the results of two rounds of a large-scale study of language attitudes and practices at the University of the Witwatersrand, Johannesburg - Nyika, Nicholus; van Zyl, Susan (South African Journal of Higher Education, 2016)
The matter of language policy in South African higher education remains contentious. Intense debate followed the promulgation of the Language Policy in Higher Education (LPHE) in 2002 which directed that all higher education institutions needed to develop language policies that presented firm commitments to developing multilingual environments in which African languages are developed as academic or scientific languages. After a period of seeming quiescence, issues around African languages have again surfaced in public debate, primarily as a result of Minister Nzimande’s call that in future it would be a requirement that every university student in South Africa learns one African language as a condition for graduation. Whether the language policy succeeds or fails is a complex matter, but one of the important factors, we suggest, relates to language attitudes and practices in particular contexts. This article revisits research into language attitudes and practices undertaken at the University of the Witwatersrand (Wits) with a view to drawing further insights into the matter of language policy in higher education, and in particular, the place of African languages. The results of the study reveal strong support for English as LOLT as well as continued strong support for Zulu as the `preferred’ African language - where an African language is supported. However, the results of the study also suggest that while the ability to understand or use an African language is considered valuable, the idea that a university should legislate in favour of an African language is not supported.